The Comprehensive Review of Deviated Septum: Anatomy, Diagnosis, and Treatment Approaches - Kudas, Zuzanna; Górka, Mateusz; Stec, Weronika; Wojtkiewicz, Anna; Piekarska, Magda; Szerej, Krzysztof (Quality in Sport, 2025)
Deviated septum, a common nasal structural abnormality, often leads to symptoms like nasal obstruction, sinusitis, and sleep disturbances, impacting respiratory function and quality of life. This clinical review emphasizes the critical role of septoplasty in the treatment of nasal septum deviation (NSD). While the nasal septum’s anatomy is essential for proper airflow, deviations can cause significant issues, particularly in severe cases. Diagnosis involves clinical evaluation and imaging to assess the extent of deviation. Septoplasty, the gold standard treatment, realigns the septum to restore normal airflow and alleviate symptoms. The review also explores advances in septoplasty techniques aimed at improving outcomes and reducing recovery time. Overall, septoplasty remains the most effective intervention for managing NSD, with ongoing research focused on refining surgical methods and enhancing patient care.